2006
DOI: 10.1158/1055-9965.epi-06-0075
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, Calcium, and Breast Cancer Risk: A Review

Abstract: Vitamin D and calcium are metabolically interrelated and highly correlated dietary factors. Experimental studies have shown their anticarcinogenic effects due to their participation in regulating cell proliferation, differentiation, and apoptosis in normal and malignant breast cells. Given the emerging interest in their potential roles in the etiology of breast cancer, we review the current epidemiologic literature on dietary and/or supplemental intakes of vitamin D, endogenous circulating levels of vitamin D,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
153
2
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(164 citation statements)
references
References 90 publications
5
153
2
4
Order By: Relevance
“…Although their biological mechanism in cancer cells remains poorly known, calcium has been recognized as a key component in the maintenance of proper cell structure and functions (Rasmussen, 1986;Friedman et al, 1989Friedman et al, , 2005Whitfield et al, 1995). Similarly, several epidemiological studies have shown that vitamin D has various anticancer effects (Martinez et al, 1996;Shin et al, 2002;Cui and Rohan, 2006;Deeb et al, 2007). Vitamin D is absorbed from diet or made in the skin by sun exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although their biological mechanism in cancer cells remains poorly known, calcium has been recognized as a key component in the maintenance of proper cell structure and functions (Rasmussen, 1986;Friedman et al, 1989Friedman et al, , 2005Whitfield et al, 1995). Similarly, several epidemiological studies have shown that vitamin D has various anticancer effects (Martinez et al, 1996;Shin et al, 2002;Cui and Rohan, 2006;Deeb et al, 2007). Vitamin D is absorbed from diet or made in the skin by sun exposure.…”
Section: Discussionmentioning
confidence: 99%
“…For breast cancer, calcium has been proposed to reduce fat-induced cell proliferation by maintaining intracellular calcium concentrations (Jacobson et al, 1989;Carroll et al, 1991;Newmark, 1994;Lipkin and Newmark, 1999;Xue et al, 1999). Vitamin D modulates calcium metabolism, inhibits cellular proliferation, induces differentiation and apoptosis and (Ziegler et al, 1991) inhibits angiogenesis in normal and malignant breast cells Xue et al, 1999;Shin et al, 2002;Cui and Rohan, 2006;Deeb et al, 2007). With regard to cervical cancer, however, only a few epidemiological studies have sought to determine the association between calcium and vitamin D and cancer risk (Ziegler et al, 1990(Ziegler et al, , 1991Liu et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…It is also increasingly important that screened women with dense breasts are advised to avoid lifestyles such as alcohol intake and exogenous hormone use that have been shown to increase cancer risk in women with dense breast. Also, consumption of food species associated with lower breast density 22,72,75,77 and physical activity 78 is encouraged as these may mitigate their risk of developing breast cancer.…”
Section: Breast Composition and Radiographic Appearancesmentioning
confidence: 99%
“…19 Some lifestyle parameters responsible for high breast density and breast cancer are controllable, 20 and consumption of food species such as vegetables, vitamin D, and calcium may have an ameliorative impact on the breast density and breast cancer risk. 21,22 Breast density is also a significant factor in interval breast cancer (cancer detected within 12 months after a normal screening mammogram), accounting for about 50%. 3,5 Women with dense breasts are 4.7 to 17.8 times at risk of interval breast cancer relative to those with non-dense breasts.…”
Section: Introductionmentioning
confidence: 99%
“…The vitamin D receptor is present in breast tissue and 1,25(OH) 2 D has anti-proliferative and prodifferentiation effects on breast cancer cells (130) . Vitamin D Vitamin D in health and diseaseand Ca are metabolically interrelated and are suggested in playing a role in the development of breast cancer by some epidemiological studies (129) . In an analysis of the first National Health and Nutrition Examination Survey Epidemiologic Follow-up Study, among a cohort of 5009 white women followed for an average of 17·3 years, several measures of sunlight exposure and dietary vitamin D intake were associated with a reduced risk of breast cancer (131) .…”
Section: Breast Cancermentioning
confidence: 99%